The integrated drainage technique of directional high-level borehole of super large diameter on roof replacing roof extraction roadway: A case study of the underground Zhaozhuang Coal Mine. (November 2020) - Li, Hong; Liu, Yanwei; Wang, Wei; Liu, Mingju; Ma, Jinkui; Guo, Xiaomin; Guo, Huaiguang
Abstract: To maintain the high-efficiency production of fully mechanized working face under the condition of highly mechanized mining and guarantee the security operations during mining process at high gassy outburst-prone mines, in most cases, the gas control methods adopted include: burying pipes in the gob, gas extraction at the stress relief zone, roof borehole with common drilling rig (RBCDR), roof borehole with directional drilling rig (RBDDR), and roof extraction roadway (RER), etc. The above method solves the gas emission problem in the mining area to some extent during the mining face. In recent years, the most popular method to deal with great depth and high gas content is RER. However, with this method, there are several adverse impacts: the work amount and investment for the roadway are large; the construction period is long; the gangue generated will cause serious pollution to the ecological environment; so on and so forth. Therefore, an integrated drainage technique of super large diameter borehole on roof (SDBR) has been proposed to replace traditional method of RER. With this technique, the directional rig with the largest power in China has been applied to make roof borehole with one-time drilling and multiple enlarged borehole diameter. Meanwhile, it can achieve the replacing effect of RER by supporting special hole-protective device. This technique has three major advantages as follows. First, while guaranteeing efficient drainage, the construction period can be shortened and the investment can be greatly reduced. Second, it can replace RER and avoid the risks in construction, transportation and outburst caused by gangue. Third, the effect of mining in the soft thick coal seam with low permeability can be ensured in a highly mechanized way. This technique can achieve simple construction process, low costs, and satisfactory outcome. Owning universal applicability, it can be widely applied in high gas and outburst mines.